2006
DOI: 10.1109/tpwrs.2006.873408
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Algorithm and Decision Tree-Based Oscillatory Stability Assessment

Abstract: -This paper deals with a new method for eigenvalue region prediction of critical stability modes of power systems based on decision trees. The critical stability modes result from inter-area oscillations in large-scale interconnected power systems. The existing methods for eigenvalue computation are time-consuming and require the entire system model that includes an extensive number of states. However, using decision trees, the oscillatory stability can be predicted based on a few selected inputs. Decision tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…In [13], a new method for eigenvalue region prediction of critical stability modes of power systems based on decision trees was presented. The paper proved that DT's are fast, easy to grow, and provide high accuracy for eigenvalue region prediction.…”
Section: Copyright © 2013 Mecsmentioning
confidence: 99%
“…In [13], a new method for eigenvalue region prediction of critical stability modes of power systems based on decision trees was presented. The paper proved that DT's are fast, easy to grow, and provide high accuracy for eigenvalue region prediction.…”
Section: Copyright © 2013 Mecsmentioning
confidence: 99%
“…Therefore, the system experiences inter-area oscillations. The system has been developed based on characteristic parameters of the European interconnected electric power system, also known as UCTE/CENTREL [23]. All generators are equipped with identical IEEE standard exciters (IEEE type DC1A excitation system).…”
Section: Power System Simulation Modelmentioning
confidence: 99%
“…With respect to the input attributes of a decision tree, it is reported that different attribute combinations may result in different data mining accuracies [12]. In order to accelerate the prediction process, it is desirable to use the least number of attributes as DT inputs while keeping an acceptable level of overall prediction accuracy.…”
Section: A Adjustment Of Priors and Selection Of Attributesmentioning
confidence: 99%
“…Later, in [11], the system post-disturbance stability has been analyzed by DT using its fast evaluation capability. In [12], a genetic algorithm was applied in feature selection to search for the best inputs to DT for oscillatory stability region prediction. In [13], Kamwa et al showed that there is a trade-off between a data mining model's accuracy and its transparency.…”
Section: Introductionmentioning
confidence: 99%